Los valores éticos y morales y su influencia en la formación integral en los estudiantes de séptimo grado de EGB de la Unidad Educativa "Digna Beatriz Cerda Neto" en el año lectivo 2016-2017 - Laverde Lomas, Kristian Marcelo (2018)
The lack of ethical and moral values in the educational field affect in the behavior of the students of the seventh years of the Educational Unit "Beatriz Cerda Neto", chipped in academic formation that was showed in the behavior of the students, a factor that allowed to strengthen the practice of values in the institution in all areas inside and outside the classroom to improve discipline, behavior and social life of the student, allowing to contribute to the development of learning for achieving academic performance optimal for educative community’s benefit, for which we considered an alternative proposal of a workshop seminary therefore we taught dynamics of integration, socio-dramas, reading and cogitation of comic strips, documents, news, workshops, conferences, videos, stories, games and cogitations on ethical and moral values. This research was based on the application of several methods such as inductive, deductive, scientific and investigative and techniques such as the survey and interview; the theoretical basis was structured with the conceptualization of different bibliographic components. They reached and contributed positively to education as a training process in the crisis of values that was presented in the classroom, making necessary the modification in the role play by education finding alternatives that allow orientation and change in teaching learning, generated a social impact that contributed to the development of learning, making the students, parents and teachers of the educative unit aware of the ethical and moral values involved in the academic formation of students, and improve conscious behaviors that education can help define an effective and effectual life project, directly benefiting 46 people among students and teachers, of which 17 are female and 29 are male, who are part of the seventh grade of EGB of the Educative Unit "Digna Beatriz Cerda Neto ".